Outsourcing w zarządzaniu usługami publicznymi - Barczak, Beata; Tyrańska, Małgorzata (Outsourcing in management of the public sector, 2005)
Implementation of reforms of local self-government in 1998 and increasing availability of various funds of the EU have encouraged authorities of public administration to search for more effective methods of management. Conditions of implementation of outsourcing method in public administration are described in the paper. Main objectives is display on the specific of outsourcing in public administration.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 185-191